View on the problem of diabetic nephropathy in children and adolescents with type 1 diabetes mellitus: the role of renin-angiotensin-aldosterone system (literature review) (part 1) - K. V. Skobeleva; L. V. Tyrtova; I. L. Nikitina; A. S. Olenev (Лечащий Врач)
Diabetic nephropathy (DN) is the main cause of the adverse prospects on the life of patients with diabetes mellitus and develops equally often in different types of diabetes mellitus. And much more often and faster DN develops in patients with early DM in childhood and puberty. The relevance and importance of this problem led to the active study by scientists of various pathogenic aspects of damage to the structure of the kidneys and microvascular bed. Currently, it is known that DN is a complex multifactorial complication which flows for a long time without clinical manifestations. Renin-angiotensin-aldosterone system makes a significant contribution to its development. These features require the creation of new diagnostic techniques for earlier detection of the pathology.